Polityka edukacyjna i językowa wobec mniejszości Sami w Norwegii - Gmerek, Tomasz (Wydawnictwo Naukowe UAM, 2016)
The article is devoted to the discussion of education and language policy as factors of ethnic assimilation and on the other hand as a factor of the revitalization of an indigenous culture. The study analyses the position of the Sami language and culture in the education system in Norway. It focuses on language as the main cultural factor of Sami ethnic identity. The author emphasizes the assimilation and marginalization process of the minority language policy in Norway and the possibilities of language revitalization in contemporary Sami society. 38 187 214 12 Studia Edukacyjne